Penyederhanaan Elemen-Elemen ISO 9000 dalam Kategori Non-Kontraktual Ditinjau dari Asas Kepastian Hukum - Seyba Nabilla Iwandha; Tarsisius Murwadji; Kilkoda Agus Saleh (Universitas Medan Area, 2020)
This article aims to find out how to apply the quality system using ISO 9000 to small industries based on applicable laws and regulations so that it still provides legal certainty for consumers. Because, often small industries ignore the application of quality in ISO 9000 because certification costs are quite expensive. The problem is focused on how the form of legal certainty given by ISO 9000 in the non-contractual category that is, without the recognition of a third party who is a certification body in terms of the principle of legal certainty. To approach this problem, theoretical references from books and journals of law can be used as guidelines for writers. The writing method used is a normative juridical approach and the writing specification is analytical descriptive. This study concludes that the application of ISO 9000 in non-contractual categories can still provide legal certainty to consumers.